Benzoin Schiff Bases: Design, Synthesis, and Biological Evaluation as Potential Antitumor Agents - Sabbah, Dima A.; Al-Tarawneh, Fatima; Talib, Wamidh H.; Sweidan, Kamal; Bardaweel, Sanaa K.; Al-Shalabi, Eveen; Zhong, Haizhen A.; Abu Sheikha, Ghassan; Abu Khalaf, Reema; Mubarak, Mohammad S. (Medicinal Chemistry, 2018)
Background: Phosphoinositide 3-kinase α (PI3Kα) is an attractive target for anticancer drug design. Objectives: Target compounds were designed to probe the significance of alcohol and imine moieties tailored on a benzoin scaffold to better understand the structure activity relation (SAR) and improve their biological activity as anticancer compounds. Methods: Chemical synthesis of the targeted compounds, biological evaluation tests against human colon adenocarcinoma (HCT-116), breast adenocarcinoma (MCF-7), and breast carcinoma (T47D) cell lines, as well as Glide docking studies were employed in this investigation. Results: A new series of 1,2-diphenylimino ethanol was successfully synthesized and characterized by means of FT-IR, HRMS, NMR, and by elemental analysis. Biological screening revealed that the newly synthesized compounds inhibit PI3Kα activity in human colon adenocarcinoma (HCT-116), breast adenocarcinoma (MCF-7), and breast carcinoma (T47D) cell lines. Results additionally showed that these compounds exhibit selective antiproliferative activity, induce apoptosis, and suppress the VEGF production. Compounds 2b, 2d, and 2g displayed promising inhibitory activity in HCT-116 suggesting that hydrophobic and/or hydrogen bond-acceptor mediate(s) ligand-receptor interaction on o- and mpositions. Furthermore, compounds 2g, 2i, 2j, and 2h, bearing hydrophobic moiety on m- and pposition, exerted high antiproliferative activity in T47D and MCF-7 cells, whereas compound 2e showed selectivity against T47D and MCF-7. Molecular docking studies against PI3Kα and caspase-3 demonstrated a strong correlation between the predicted binding affinity (ΔGobsd) and IC50 values of prepared compounds for the caspase-3 model, implying that the cellulous inhibitory activity was caspase-3-dependent. Moreover, Glide docking against PI3Kα identified Ser774, Lys802, E849, V851, and Asp933 as key binding residues. Conclusion: The series exerted a potential PI3Kα inhibitory activity in human carcinoma cell lines expressing PI3Kα.
Keywords: HCT-116